The Effect of Work Discipline on the Work Productivity of PT. Dayup Indo Jakarta - Mardiana, Mardiana; Fa’uzobihi, Fa’uzobihi; Partimah, Partimah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to determine work discipline on the work productivity of PT. Dayup Indo Jakarta. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires, and library data. In this study using a saturated sampling method used a total of 38 employees of PT. Dayup Indo Jakarta, using simple linear regression data analysis techniques. The results of this study show that there is an influence between work discipline on the work productivity of PT. Dayup Indo Jakarta and work discipline have a moderate positive effect and have an influence contribution of 31.6% on employee work productivity variables. The results of this study are expected to contribute to future research.